Polanyi and social economy - Isaac, Barry L. (A Handbook of Economic Anthropology, 2022)
Substantivism stemmed from the writings of Hungarian lawyer-turned-historian Karl Polanyi, who argued that capitalism is a historically unique kind of economy that is disembedded from the social matrix. By implication, the socially embedded pre-capitalist economies studied by anthropologists, historians and classicists cannot be understood using the formal economics developed to analyze capitalist economies. Rather, new tools for analysing their 'substantive' economies must be employed. Substantivism was championed in economic anthropology by economist-turned-anthropologist George Dalton and became the reigning paradigm in the subfield during the 1960s. Formalism arose in opposition, arguing that capitalist and pre-capitalist economies differ in degree, not in kind, and thus can all be analysed using the tools of microeconomics. Formalism largely displaced substantivism during the 1970s and 1980s as anthropologists increasingly focused on the economic integration of the world's peasant sectors into their national and regional economies.
Economics; Anthropology

Capitalism and Crisis: Thinking Through Capitalist Crisis with Schumpeter and Polanyi - Delanty, Gerard (Capitalism, Democracy, Socialism: Critical Debates, 2022)
The chapter offers an analysis of capitalist crisis through a reading and discussion of two seminal texts on capitalism, Joseph Schumpeter’s Capitalism, Socialism and Democracy [1943] and Karl Polanyi’s The Great Transformation [1944]. These inspiring works on economic history and social theory offer profound insights into the nature of capitalist crisis. Although written in the mid-twentieth century many of the insights in these books are of relevance to the current situation as capitalism undergoes another revulsion. While the two authors were very different – Polanyi a left-wing critic of capitalism; Schumpeter a politically right-wing economist who favoured capitalism – both were influenced by Marx’s analysis of capitalism and have helped to shape the debate on the crisis of capitalism. Indeed, Schumpeter was convinced Marx was mostly right in his prediction of the end of capitalism and the triumph of socialism. The chapter begins with a brief account of the Marxist theory capitalism in order to contextualise the discussion of the two theorists.
Political Science; Philosophy
Keywords: MARX; Karl; 1818-1883; Polanyi; SCHUMPETER; Joseph Alois; 1883-1950; capitalism; crisis